High Efficient Hole Extraction and Stable All‐Bromide Inorganic Perovskite Solar Cells via Derivative‐Phase Gradient Bandgap Architecture. Issue 5 (12th March 2019) - Tong, Guoqing; Chen, Taotao; Li, Huan; Song, Wentao; Chang, Yajing; Liu, Jingjing; Yu, Linwei; Xu, Jun; Qi, Yabing; Jiang, Yang
Abstract : Inorganic perovskite materials have demonstrated outstanding performance in the field of photovoltaic devices due to their superior charge carrier transport properties and excellent thermal stability. In particular, the inorganic perovskite derivative phases show special properties in terms of phase stability and optoelectronic application, especially in the phase transition investigation. However, their commercial applications still face challenges due to the large recombination at the interface, resulting in poor efficiency and metastable phases such as iodide perovskite existing in the film. Herein, an all‐bromide inorganic perovskite solar cell has been developed by introducing the derivative phases (CsPb2 Br5 and Cs4 PbBr6 ) to construct gradient bandgap architecture. This graded heterojunction device is realized with a controllable sequential vapor deposition procedure. The valance band maximum elevates gradually with the presence of derivative phases and effectively blocks electrons and boosts the hole extraction efficiency at the counter electrode, which promotes charge separation and reduces the interface recombination. Ultimately, an impressive power conversion efficiency of 10.17% is achieved through a CsPbBr3 /CsPbBr3 ‐CsPb2 Br5 /CsPbBr3 ‐Cs4 PbBr6 architecture strategy with excellent stability above 3000 h (85% of initial performance) in a humid environment (@RH ≈45%) and 700 h (83% of initial efficiency) under thermal conditions (@ 100 °C). Abstract : All‐bromide perovskite solar cells with gradient bandgap are constructed by vapor deposition procedure accompanying with the derivative‐phase to boost the hole extraction efficiency and stability. An impressive power conversion efficiency of 10.17% is obtained via a vapor deposition method for a hole transfer layer‐free inorganic PSC. The device also exhibits an excellent humidity and thermal stability for more than 3000 h in RH ≈45% environment and 700 h at 100 °C. These results pave a great advancement in all inorganic PSCs and also open the window of perovskite derivative‐phase.